2006
DOI: 10.1016/j.cub.2006.06.061
|View full text |Cite
|
Sign up to set email alerts
|

Control of Axonal Sprouting and Dendrite Branching by the Nrg-Ank Complex at the Neuron-Glia Interface

Abstract: Neurons are highly polarized cells with distinct subcellular compartments, including dendritic arbors and an axon. The proper function of the nervous system relies not only on correct targeting of axons, but also on development of neuronal-class-specific geometry of dendritic arbors [1-4]. To study the intercellular control of the shaping of dendritic trees in vivo, we searched for cell-surface proteins expressed by Drosophila dendritic arborization (da) neurons [5-7]. One of them was Neuroglian (Nrg), a membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 26 publications
4
101
1
1
Order By: Relevance
“…An alternative mechanism by which UNC-44 regulates SAX-7 function may be in controlling SAX-7 localization. Previous studies show that ankyrin is required to maintain L1 in some axon tracts in the mouse and, more recently, in Drosophila (Scotland et al 1998;Yamamoto et al 2006). However, our data do not support this idea.…”
Section: Unc-44 and Sax-7 Are Not Interdependent For Protein Localizacontrasting
confidence: 99%
See 1 more Smart Citation
“…An alternative mechanism by which UNC-44 regulates SAX-7 function may be in controlling SAX-7 localization. Previous studies show that ankyrin is required to maintain L1 in some axon tracts in the mouse and, more recently, in Drosophila (Scotland et al 1998;Yamamoto et al 2006). However, our data do not support this idea.…”
Section: Unc-44 and Sax-7 Are Not Interdependent For Protein Localizacontrasting
confidence: 99%
“…Previous analyses in the mouse and Drosophila revealed that ankyrin mutants exhibit phenotypes similar to the respective mouse L1 and Drosophila neuroglian mutants, suggesting that both ankyrin and L1CAM function in the same process (Scotland et al 1998;Yamamoto et al 2006). Together with data showing that UNC-44 binds SAX-7, we hypothesize that a mechanism by which UNC-44 regulates SAX-7 function may be in providing SAX-7 anchorage to the spectrin-actin cytoskeleton, thereby increasing SAX-7-mediated adhesion.…”
Section: Unc-44 and Sax-7 Are Not Interdependent For Protein Localizasupporting
confidence: 58%
“…We found that there were no differences between the two groups (wild type: lateral, 352.3 Ϯ 25.8; medial, 980.3 Ϯ 9.5; KO: lateral, 360.0 Ϯ 16.5; medial, 950.3 Ϯ 41.9 KO; n ϭ 3 in each group). We concluded that excess collateralization of hypoglossal axons occurs because of delayed myelination during the early postnatal period in KO mice and is lost later by selective pruning of excess axonal branches (22,23).…”
Section: Lack Of Effect Of Cntf On Facial Motor Neuron Survival In Rementioning
confidence: 88%
“…Drosophila da dendrite morphogenesis can be divided into two components: an intrinsic program establishing a basic dendritic pattern, and an extrinsic program influenced by support cells (Yamamoto et al 2006) and competition between dendrites from similar neurons (Grueber and Jan 2004). The phenotypic analyses of a rapidly expanding number of genes that influence dendrite morphogenesis provide evidence that the intrinsic program can be further subdivided into genes that control discrete aspects of dendrite formation.…”
Section: Regulation Of Drosophila Dendrite Developmentmentioning
confidence: 99%